Response of 'PBW 343' wheat (Triticium aestivum) to increasing levels of residual alkalinity in irrigation water in semi-arid regions - CHOUDHARY, O P; GHUMAN, B S; SAROA, G S (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was carried out during 2002-05 in a sandy loam soil to study the response of 'PBW 343' wheat (Triticum aestivum L. emend. Fiori & Paol.) to irrigation waters having 4 levels of residual sodium carbonate (0,3,6.5, 10 me/litre). Increase in residual sodium carbonate of irrigation water significantly increased pH, sodium adsorption ratio and exchangeable sodium percentage of the soil up to 60 cm depth and decreased the grain yield of 'PBW 343' in all the 3 years. The response was influenced by the number of irrigations and amount of rainfall in a year. Relative to good quality canal water, irrigation with waters having residual sodium carbonate values of 3,6.5 and 10 mellitre decreased the grain yield by 0.16 and 0.18 tonnesha, 0.50 and 0.48 tonnesha and 1.22 and 1.3 1 tonnesha during 2002-03 and 2004-05, respectively. In 2003-04 relatively higher corresponding decline in grain yield (0.64,0.85 and 1.95 tonnesha) was observed. This can be attributed to low rainfall (73 mm) in 2003-04 compared to 200 mm and 154 mm rainfall received during 2002-03 and 2004-05 respectively. The results show that PBW 343 can be grown with irrigation waters having residual sodium carbonate up to 6.5 mellitre without any substantial loss in grain yield.